A web-based learning system for reconceptualization : basic electric circuits - Yahaya, Nazli (2003)
This paper describes a learning system using an approach to induce hierarchical cognition for reconceptualization in Basic Electric Circuits. The concept-building model, which ascribes interactive multimedia to cognitive processes, is built upon the knowledge framework as a basis to design learners’ interaction at the interface. Cognitive processes are systematically activated over increasing levels of cognition and matched with learner activities of increasing complexity. The four-phase learning approach, namely, @cognitive conflict, (ii)testing presented new knowledge, (iii)discriminating new and old knowledge, and, (iv) declaring and articulating new concepts, is included in the cognition hierarchy of the concept-building model. Sensory activities of reading and observing an interface which are predominantly text, graphics and animations, of electrical phenomena stimulates conceptual recall as preparation for subsequent metacognitive activities involving increasing physical interactions at the interface. High learnercontrolled activities include encompass reading text guide, dragging and dropping graphical objects to specified coordinates, observing effects of construction, and entering input of voltage measurements. Interactive discussions of question and answer options buttons with explanatory feedback prompts help learners to mentally discriminate and clarify their new knowledge. As a final measure for cognitive consolidation, learners write opinions to contend true or false assertions of the different aspects of electrical concepts